2017
DOI: 10.22489/cinc.2017.374-228
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Pulmonary Vein Electrophysiology and Atrial Fibrosis Determines Driver Location

Abstract: Patients exhibit a range of pulmonary vein (PV) and fibrosis properties, but their individual and combined effects on arrhythmia inducibility and maintenance mechanisms is unknown. We aim to predict locations of high phase singularity (PS) density using a combination of PV electrophysiology and fibrosis measurements. We used a bilayer computational human atrial model with interstitial fibrosis based on delayed-enhancement MRI (DE-MRI), including high or low levels of fibrosis. PV action potential duration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A simulation test with a computational human atrial model revealed that the greatest AF inducibility could be found in cases with circular fibers at the PV ostium. 4,5 Dispersion of the ERP and the dynamic changes in the circumferential conduction delay within the PVs may lead to anisotropic conduction and reentry that can initiate AF. In this tissue of the journal, Kawai et al demonstrated that a circumferential intra-PV conduction delay arose at the onset of AF in response to a single extrastimulus at AF inducible sites.…”
Section: Electrophysiologic Characteristics Of the Pvsmentioning
confidence: 99%
See 1 more Smart Citation
“…A simulation test with a computational human atrial model revealed that the greatest AF inducibility could be found in cases with circular fibers at the PV ostium. 4,5 Dispersion of the ERP and the dynamic changes in the circumferential conduction delay within the PVs may lead to anisotropic conduction and reentry that can initiate AF. In this tissue of the journal, Kawai et al demonstrated that a circumferential intra-PV conduction delay arose at the onset of AF in response to a single extrastimulus at AF inducible sites.…”
Section: Electrophysiologic Characteristics Of the Pvsmentioning
confidence: 99%
“…Not only a longitudinal PV‐LA conduction delay but also a circumferential conduction delay contributes to AF initiation. A simulation test with a computational human atrial model revealed that the greatest AF inducibility could be found in cases with circular fibers at the PV ostium 4,5 . Dispersion of the ERP and the dynamic changes in the circumferential conduction delay within the PVs may lead to anisotropic conduction and reentry that can initiate AF.…”
Section: Electrophysiologic Characteristics Of the Pvsmentioning
confidence: 99%
“…This physiological variation in myofiber direction could, in theory, render the RVOT more vulnerable to myofiber disarray, particularly in the context of structural abnormalities. [ 25 , 26 ].…”
Section: The Right Ventricular Outflow Tractmentioning
confidence: 99%
“…They also reported that fiber direction at the PV ostium was more complex and disorganized than that at the distal PV. Recently, simulation tests with computational human atrial model revealed that the greatest AF inducibility occurred for cases with circular fibers at the PV ostium 12,13 . Taken together, AF initiation would be determined by an initial anisotropic conduction in relations to location and CI of an ectopic excitation, and surrounding histological backgrounds.…”
Section: Discussionmentioning
confidence: 99%